2020
DOI: 10.1111/jre.12795
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inflammatory biomarkers and growth factors in gingival crevicular fluid at different healing intervals following non‐surgical periodontal treatment: A systematic review

Abstract: Background: Non-surgical periodontal treatment (NSPT) is widely employed for the treatment of periodontal disease and yields significant clinical improvements. Gingival crevicular fluid (GCF) can be used to profile health and disease, and recent technological advances, such as multiplex bead immunoassays, are promising in identifying a wider array of GCF factors with the ultimate aim to predict the treatment response. Objective: The aim of this systematic review was to compare the expression of GCF markers usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…The samples were read using a Luminex MAGPIX analyser (Luminex; R&D systems), and the concentrations for each marker were reported in pg/ml. The 27 GCF markers investigated were as follows 6,7 : angiopoietin-1 (Ang-1), bone morphogenic protein-2 (BMP-2), epidermal growth factor (EGF), basic fibroblast growth factor (FGFb), interferon-gamma (IFNγ), interleukin-1α (IL-1α), interleukin 1β (IL-1β), interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-10 (IL-10), matrix metalloproteinase-1 (MMP-1), matrix metalloproteinase-3 (MMP-3), matrix metalloproteinase-8 (MMP-8), osteopontin (OPN), platelet-derived growth factor-AA (PDGF-AA), derived growth factor-BB (PDGF-BB), tissue inhibitor metalloproteinase-1 (TIMP-1), tumor necrosis factor-alpha (TNFα), receptor activator of nuclear factor kappa-Β (RANKL), vascular endothelial growth factor (VEGF), bone morphogenic protein-7…”
Section: Multiple Bead Immunoassaymentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were read using a Luminex MAGPIX analyser (Luminex; R&D systems), and the concentrations for each marker were reported in pg/ml. The 27 GCF markers investigated were as follows 6,7 : angiopoietin-1 (Ang-1), bone morphogenic protein-2 (BMP-2), epidermal growth factor (EGF), basic fibroblast growth factor (FGFb), interferon-gamma (IFNγ), interleukin-1α (IL-1α), interleukin 1β (IL-1β), interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-10 (IL-10), matrix metalloproteinase-1 (MMP-1), matrix metalloproteinase-3 (MMP-3), matrix metalloproteinase-8 (MMP-8), osteopontin (OPN), platelet-derived growth factor-AA (PDGF-AA), derived growth factor-BB (PDGF-BB), tissue inhibitor metalloproteinase-1 (TIMP-1), tumor necrosis factor-alpha (TNFα), receptor activator of nuclear factor kappa-Β (RANKL), vascular endothelial growth factor (VEGF), bone morphogenic protein-7…”
Section: Multiple Bead Immunoassaymentioning
confidence: 99%
“…Our group has previously identified a broad array of both inflammatory and regenerative markers present in the GCF following surgical treatment of intrabony sites 6 and following non-surgical treatment of conventional periodontitis sites. 7 In the present study, this wide array of markers was used to profile the GCF of intrabony defect sites and periodontally healthy sites, using multiplex immunoassays.…”
mentioning
confidence: 99%
“…In a systematic review and meta-analysis, it was reported that the levels of IL-1β, IFN- γ, MCP-1, and IL-6 in gingival crevicular fluid of periodontitis patients were higher than in healthy individuals, while no differences were observed for IL-12 and IL-17 [ 21 ]. Further, it was reported that the levels of IL-1β and IL-17 significantly decreased after periodontal treatment, while another systemic review reported reduced levels of, among others, IL-1β, IL-6, TNF-α, IFN- γ, and MCP-1, six to eight weeks after periodontal treatment [ 24 ]. Thus, the inflammatory mediators measured in our study have previously been linked to periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“… Human studies Prospective clinical studies reporting on the expression of Wnt signaling agonists: Wnts, Norrin, R‐spondins (Rspo), and antagonists: Dickkopf proteins (Dkks), secreted frizzled‐related proteins (sFRPs), Wnt‐inhibitory factor 1 (WIF‐1), Wise/SOST, Cerberus, insulin‐like growth factor‐binding protein 4 (IGFBP‐4), Shisa, Wnt‐activated inhibitory factor 1 (Waif1/5 T4), adenomatosis polyposis coli down‐regulated 1 (APCDD1), and Tiki1 in the GCF, serum and/or gingival tissue Expression levels reported before and early (≤30 days) or late (3 months) after NSPT Only studies with at least 5 subjects per group were included in this review For this analysis, the follow‐up time points were classified as early, when the sampling occurred less than 30 days following the intervention and late, when the sampling occurred more than 3 months following the intervention 31,32 …”
Section: Methodsmentioning
confidence: 99%